Legal challenges to the protection of labor rights of refugees in the digital age - Vakhoneva, Tetyana M.; Mykolayets, Dmytro A.; Hryshyna, Yuliya M.; Yurovska, Viktoriia V.; Dyachenko, Olha A. (Legality : Jurnal Ilmiah Hukum, 2023)
The relevance of the problem of protection of the rights of persons granted refugee status is due, in particular, to the fact that the increase in the number of refugees and related political, economic, and social problems confirms the need to reassess and rethink the legal status of this category of persons and to develop a new approach to the analysis and solution of the refugee problem at both international and regional levels. The situation in Ukraine also confirms the fact that not all states are ready to cooperate within the framework of international law and prevent human rights violations, which, in turn, can lead to an increase in the number of refugees. Therefore, the issue of protecting their rights does not lose relevance in scientific research. The purpose of the article is to study the general features of obtaining refugee status and the exercise of the right to work by such persons. The author analyzes the normative sources of international and national law on the relevant topics. In addition, the author examines the practical aspects of the exercise of the right to work by refugees, in particular the problems faced by such persons and suggests possible solutions to existing problems. The leading method used for the study is the formal legal method. Its application determined the feasibility and validity of the study. This method was used in the analysis of legal acts regulating the protection of labor rights of refugees, namely: acts of international law, legislation of the EU member states, Asian countries, as well as national law of Ukraine.